Determination of Traffic Induced Noise Pollution and its Impact on City Dwellers in the Chittagong City Area - Uddin, Mohammad Nasir; Hoque, Md. Shahidul; Islam, Muhammad Alamgir (European Scientific Journal, ESJ, 2018)
Chittagong, the port city of Bangladesh, is one of the nosiest cities of the country. Extreme noise is very inimical for human health and environment. Noise pollution implies a discomfort and restlessness caused to humans by unwanted high intensity sound. Motorized traffic is one of the major sources of producing noise in Chittagong city. The present paper deals with determining the level of the noise pollution in Chittagong city area and its impact on city dwellers. In this study noise levels have been measured with digital sound level meter at eight different places of Chittagong city from 6:00 am to 9:00 pm during working days. Time weighted average noise level has been measured at the road side. The data have been analyzed to compute the average, maximum and minimum noise level in decibel (dB) with respect to traffic volume. From the study it was observed that the highest noise level in the road side in Chittagong city was 112 dB found at New Market and 2 No gate traffic area, which for exceeded the acceptable limit of 60 dB set by the Government of Bangladesh and minimum sound level 67 dB was recorded at GEC traffic area. The highest average value is 109.66 dB found at 2 No gate traffic area and lowest average value is 68.7 dB found at GEC traffic area. Questionnaire survey was done during the study to determine the health impact on the city dwellers. Most of the common problems, the dwellers suffering from noise pollution are headache, bed temper, sleeplessness, aggravation, hearing problems etc.